Stability-Indicating RP-HPLC Method for Simultaneous Determination of Olmesartan Medoxamil and Pioglitazone in Fixed Dose Combination Tablet Dosage Form - Sengupta, Pinaki; Das, Ayan; Kumar Pal, Tapan (Asian Journal of Chemistry, 2010)
The aim of the present study is to develop and validate a novel, simple, selective and sensitive stability indicating reverse phase HPLC method for the simultaneous determination of olmesartan medoxamil (OLM) and pioglitazone (PIO) in tablet dosage form after being subjected to different stress conditions, such as hydrolysis (0.1 N HCl and 0.1 N NaOH), oxidation (30 % H2O2), heat (80 ºC for 48 h) and photolysis (UV, 254 and 366 nm). The validation studies were carried out as per the International Conference on Harmonisation (ICH) and United State Pharmacopoeia (USP) guidelines. An isocratic HPLC method was developed to separate olmesartan and pioglitazone from the degradation products, using a Hiber C18 column (250 mm × 4.60 mm, 5 μm). A mixture of 10 mM KH2PO4 buffer (pH 4.4) and acetonitrile (50:50, v/v) was used as mobile phase. The flow rate was 1.0 mL/min and the UV detection was carried out at 230 nm. Retention time for olmesartan and pioglitazone were 5.58 and 10.73 min, respectively. A linear response was observed in the range of 0.10-200.00 μg/mL (r2 > 0.99) for both the drugs. Drugs were decomposed in acid, base and 30 % H2O2 but were found to be stable in heat and photolytic stresses. The method was validated in terms of linearity, precision, accuracy, specificity, limit of detection and quantitation and robustness. The procedure was found to be specific, linear, precise (including intra and inter day precision), accurate and robust. Applicability of the method has been illustrated performing the assay of a fixed dose combination tablet.